Analysis Of The Needs Of The Ilohungayo Village Community In The Utilization Of Sediment As An Alternative Construction Material In Gorontalo Regency - Desei, Frice L.; Purnamawati, Purnamawati; Hamsu Abdul Gani (International Journal of Education, Vocational and Social Science, 2024)
The need for more public knowledge about using local materials encourages an educational approach to introduce sediment as an alternative material for construction materials, either as a substitute for clay in making bricks or as a filling material. This study aims to analyze the needs of the Ilohungayo Village community regarding educational models that can improve their understanding and skills in utilizing dredged sediment from Lake Limboto, as well as evaluating its potential use as an alternative material for basic brick materials and other construction materials. The method used is a preliminary study with a quantitative descriptive approach. The study results showed that only 18.33% of respondents knew or had used sediment, while 81.67% needed to learn sediment utilization. The low utilization of sediment is due to the need for more knowledge and training in the community.